Digest of educational statistics of Guyana 1998-1999 (Ministry of Education. Planning Unit GeorgetownGY, 1999)
Presents information on the educational institutions in the country ranging from nursery to univeristy level for 1998-1999. Supplies also significant indicators which relate to the previous year e.g. tables on repeators, admissions, withdrawals and drop-outs.
Keywords: EDUCATIONAL STATISTICS